A fragmentação de hábitat influencia as estruturas filogenética e bioacústica das anurocenoses? - Ferreira, Luiz Fernando (2023)
Fragmentation is identified as the main cause of biodiversity decline, especially of amphibians, the most endangered group of vertebrates in the world, due to their biological attributes. However, we still do not fully understand the effects of fragmentation on biological communities, especially with regard to their bioacoustic aspects. In addition, classical methods for measuring biodiversity, based on richness and abundance, although important, may be ineffective to fully understand how communities respond to fragmentation. In this context, ecophylogenetics, a recent area of biology that integrates ecology and evolution, has been proposing new approaches to estimate the diversity and structure of these communities based on the phylogenetic relationships between the species in a given region. Thus, our objective was to test the hypothesis that forest fragmentation would act as a habitat filter, reducing the phylogenetic diversity of Atlantic Forest anurocenoses, through the selection of closely related species (clustered phylogenetic structure) and with similar vocalization parameters (grouped phenotypic structure). For that end, we surveyed the anuran compositions of 18 buffers within a fragmentation gradient in the Corredor CantareiraMantiqueira, using autonomous acoustic recorders, from which we also obtained values of four bioacoustic parameters (one temporal and three spectral) of the respective species. From these data, we tested through the metrics of phylogenetic Diversity (SES.PD), mean distance between pairs (SES.MPD), mean distance between the closest taxon (SES.MNTD) and the Horn-Morisita overlap index, the effect of fragmentation on the phylogenetic structure and of the niche overlap of the anurocenoses studied here. We recorded 40 frog species including Aquarana catesbeiana, an invasive frog. Our analyzes demonstrated that: (i) fragmentation influenced phylogenetic diversity, increasing this diversity as forest cover decreased; (ii) fragmentation does not influence the phylogenetic structure of the anurocenoses studied (iii) acoustic niche overlap between species is high regardless of the percentage of forest cover; and (iv) there was extensive overlapping of acoustic niches (very similar bioacoustic parameters), regardless of the degree of relatedness of the species, indicating that the premise that competition is greater between related species is not always true